Wound Care using Calcium Alginate as a Primary Dressing to Overcome Tissue Integrity Disorders in Type II DM Patients - Patrisia, Eriza Eka; Aprilyadi, Nadi; Wibowo, Wahyu Dwi Ari; Wijaya, Sapondra (Jurnal Surya, 2023)
Introduction: Disruption of skin and tissue integrity is the most common problem in diabetes mellitus (DM) patients. This disorder causes damage to the skin and tissue. Non-pharmacological treatment of tissue integrity disorders through wound care. Calcium alginate dressings are reported to accelerate wound healing, facilitate extracellular matrix secretion, granulation tissue formation, are anti-bacterial, and are able to absorb large amounts of wound exudate. This study aims to determine the effectiveness of calcium alginate as a primary dressing to correct tissue integrity disorders in patients with type 2 diabetes mellitus in the working area of the Citra Medika Health Center, Lubuklinggau City.Methods: Descriptive research, with a case study approach, using 2 subjects with a medical diagnosis of DM, which shows nursing problems with tissue integrity disorders. This research was carried out by providing wound care using calcium alginate 3 times within 1 week. The outcome measured in this research is the existence of network integrity according to the SLKI.Results: Subject 1 showed improvement on day 5 with a decrease in the area of the wound on the middle finger of 0.2 cm, while subject 2 did not show changes in the entire wound after wound treatment. The difference in improvement in the wounds of the two subjects was influenced by various factors including regular use of DM medication, diet, and physical activity of the two subjects.Conclusion: Wound treatment using calcium alginate massage shows a reduction in tissue integrity disorders, with supporting factors being the regular use of DM medications, diet and physical activity.